 The effect of the length and time of the test on the psychometric properties of thetest and on the level of performance from the point of view of university professors -  Manar Farouk Aziz Al-Farouk ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
In this study, the psychometric characteristics of the test were defined and the effect of the length and time of the test on them was studied, as well as the effect of the performance level of students from the teachers' point of view. The university professors’ point of view, test performance strategies, the difference in length and time of the test, the level of students’ performance from the university professors’ point of view. This questionnaire was relied upon to obtain data to complete the scientific aspect of the study. Among the most important findings of the study